Exploring the Decision-Making Processes: How Urban Indonesia's Middle-Class Prioritizes Convenience and Cost on Live-Streaming Commerce - Pradika, Mohammad Fawaid; Aristawati, Talitha; Sabila, Radifa Husna; Pambudi, Satria Aji; Marjorie, Maria Audrey (CHANNEL: Jurnal Komunikasi, 2025)
This study explores the decision-making process of middle-class consumers in Surabaya, Indonesia, when purchasing primary needs through Shopee Live, an emerging live-streaming commerce feature. Drawing on Kotler and Armstrong’s five-stage model of consumer decision-making, this qualitative research explores how internal motivations, external constraints, and digital platform features shape online shopping behavior. In-depth interviews with purposively selected informants were conducted and analyzed using thematic analysis. The findings reveal that the problem recognition stage is influenced by internal factors such as discomfort with offline shopping and limited time, as well as external barriers like store distance and additional offline costs. During the information search stage, consumers rely on Shopee Live hosts, real-time viewer comments, and product reviews. At the alternative evaluation stage, decision-making is shaped by price comparisons, discount availability, user interface ease, and product variety. The purchase decision is ultimately driven by price competitiveness, transactional convenience, and the interactive nature of the live-streaming format. In the post-purchase stage, behavior ranges from product returns and negative reviews among dissatisfied consumers to enthusiastic recommendations among highly satisfied buyers. The study contributes to consumer behavior theory by demonstrating how live commerce integrates digital interactivity with traditional evaluative mechanisms. Practically, it offers strategic insights for digital marketers seeking to engage middle-class urban consumers through affordability, user experience, and trust-building features.